Relation Between Temperament and School Adjustment in Spanish Children: A Person-Centered Approach - Ato, Ester; Fernández-Vilar, María Ángeles; Galián, María Dolores (Frontiers in Psychology, 2020)
The aim of this study was to examine from a person-centered approach the impact of temperament on academic achievement and sociometric status in a sample of 6-7 year-old Spanish children. To measure children´s temperament in early childhood, parents were given TMCQ (Temperament in Middle Childhood Questionnaire), while sociometric status and academic achievement were requested for children´s teachers. Using latent profile analysis (LPA) 4 temperament profiles were found. Children belonged to the “Negative/Undercontrolled” profile showed a higher probability of academic failure and were more rejected, and children included in the profile “Sociable/High regulated” showed higher academic scores and a lower probability of being rejected by their peers. Several implications in the Spanish educational context are discussed.